Prototype Media Tempat Sampah Dengan Teori P-Process - Donny Tri Wahyudi (FORIKES, 2020)
Making waste media as a health promotion is fundamental to provide an understanding of waste processing, sorting and handling. This study aims to analyze health education with media created based on the P-Process theory. This type of observational analytic study was cross sectional. The stages of research carried out based on p-process theory to the prototype stage with media was tested through quantitative approaches with Wilcoxon sign test and qualitative interviews with in-depth interviews.The results was showed that health education with the media of the trash can effectively increased knowledge by p = 0.02 with α